2001
DOI: 10.1159/000046831
|View full text |Cite
|
Sign up to set email alerts
|

Injury- and Use-Related Plasticity in Adult Auditory Cortex

Abstract: After restricted cochlear lesions in adult animals the frequency selectivity of neurons in the cortical region deprived of its normal input by the lesion is changed such that the region is occupied by expanded representations of adjacent (perilesion) frequencies. These changes reflect a dynamic process of reorganization (plasticity) and are not explicable as passive consequences of the lesion. Analogous plasticity of cortical frequency selectivity and organization is seen following behavioural training that en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…In cats with high-frequency hearing loss, neurons in auditory cortex originally tuned to high frequencies alter their tuning to process inputs from intact nearby portions of the cochlea [2,22]. Similar neuroplastic changes occur in humans with SNHL: difference limens for frequency are altered in a manner consistent with a neuroplastic expansion of the representation of sounds below the high-frequency hearing loss and the correspondingly reduced representation of higher frequencies [23].…”
Section: Cortical Plasticity and Perceptual Learningmentioning
confidence: 88%
“…In cats with high-frequency hearing loss, neurons in auditory cortex originally tuned to high frequencies alter their tuning to process inputs from intact nearby portions of the cochlea [2,22]. Similar neuroplastic changes occur in humans with SNHL: difference limens for frequency are altered in a manner consistent with a neuroplastic expansion of the representation of sounds below the high-frequency hearing loss and the correspondingly reduced representation of higher frequencies [23].…”
Section: Cortical Plasticity and Perceptual Learningmentioning
confidence: 88%
“…Thus, the perception of simple attributes of sound (pitch, duration) and complex ones (sound patterns, speech sounds) improves with training. Improved perception is accompanied by changes in the auditory cortex, similar to those induced by environmental experience and injury (Irvine et al, 2001). A typical result is that following active training on a task (e.g., discriminating one sound from another) with a particular target stimulus (e.g., a tone of a given frequency; a speech sound discriminable based on a specific cue such as voicing; a location cue), participants can distinguish stimuli they previously could not.…”
Section: Perceptual Learningmentioning
confidence: 99%
“…This means that even in adult animals, higher levels of the auditory system will change their function in response to the type of information received from the auditory periphery. When information related to certain frequencies is no longer received, its representation in the cortex is also lost (Irvine, Rajan, & Brown, 2001). Similar changes, known as cortical-map plasticity, occur following training.…”
Section: Reorganization Following Sensory Loss and Injurymentioning
confidence: 99%
“…A maladaptive response to this loss of input causes expansion of the tonotopic map so that this affected portion now becomes responsive to the adjacent frequency at which hearing threshold is normal -the lesion-edge frequency ( Figure 7). Of relevance for human neuroimaging studies, animal research has shown that a restricted cochlear lesion in adult animals drives neuroplastic changes in the frequency gradient within primary auditory cortex (Robertson and Irvine, 1989;Kaas, 1991, Rajan et al, 1993Schwaber et al 1993;Irvine et al, 2001). One theory of TI proposes that it is a consequence of such cortical reorganisation (e.g., Salvi et al, 2000a).…”
Section: Iii) Reorganisation Of the Cortical Tonotopic Mapmentioning
confidence: 99%